Analysis of the Heavy Metal Levels (Cd, Fe, Hg and Pb) at Losari Beach Tourism Reclamation of Makassar - Firnanelty, Firnanelty; Chadijah, Sitti; Adawiah, Syarifah Rabiatul; Firdaus, Firdaus; Nugraha, Muh. Imam Dyan Nugraha Imam Dyan (Indonesian Journal of Chemical Research, 2022)
The process of stockpiling reclamation areas and disposing of waste streams can pollute the environment and cause the attendance of dangerous heavy metals. In this research was conducted to determine heavy metals Cd, Fe, Hg, and Pb levels in water and sediment on Losari beach. The method used was an atomic absorption spectrophotometer. The result showed that the levels of Cd and Fe in the water for the north point were 0.0278 and 0.0432 mg/L, the south point was 0.0031 and 0.0674 mg/L, the point around the platform showed 0.0028 and 0.0534 mg/L and the levels of sediment were 0.0010 and 31.2417 mg/L. The levels of Hg and Pb in water were 0.0235 and 0.0390 mg/L (north point) 0.0105 and 0.0420 mg/L (south point) 0.0027 and 0.0460 mg/L (around the platform), sediments were 0.0027 and 0.071 mg/L. The result concluded that the concentration of Cd had crossed the threshold only at the north point namely 0.01 mg/L, while the concentration of Fe that crossed the threshold was only in sediment namely 20 mg/L. The level of Hg and Pb pollution in the water and sediment of Losari beach tourism is polluted because it exceeds quality standards.